PROBLEMATIK PEMBELAJARAN DARING MATA KULIAH BAHASA INDONESIA - Ernawati, Yeni (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
This study aims to describe the problematics of online learning in Indonesian language courses. This research is descriptive research. The aim of this research is problematic learning in Indonesian language courses online. The data in this study are learning problems that occur in Indonesian language learning activities. Researchers make observations and documentation to collect data. Based on observations and data collection, it is known that online learning in Indonesian courses, there are several learning problems. The problematic of online learning that occurs in the learning process of Indonesian courses occurs in the learning components. Learning problems occur in (1) learning facilities or media and infrastructure, namely e-learning and internet access; (2) presentation of material and use of learning methods; (3) discussion activities, and (4) learning assessment. During the learning process by establishing good communication with students, as well as efforts to hold effective learning, the teacher determines learning techniques that can minimize these problems.